Clinical application of kampo medicine (rikkunshito) for common and/or intractable symptoms of the gastrointestinal tract - Tominaga, Kazunari; Arakawa, Tetsuo (Frontiers in Pharmacology, 2015)
Gastroenterological reflux disease and functional dyspepsia are usually treatable using Western medical practices. Nonetheless, some cases present with intractable symptoms that are not amenable to these therapies. Treatment with kampo, a traditional Japanese medicine, recently has been proposed as an alternative therapy for use in combination with the Western practices. In general, traditional Japanese medicines have been used empirically for intractable symptoms correctively designated as “general malaises”. Accumulating lines of evidence, including basic and clinical researches, have demonstrate detailed mechanisms where traditional Japanese medicines exert pharmacological action to improve symptoms. Therefore, traditional Japanese medicines have been gaining use by various medical doctors as the specific modes of pharmacological action are recognized. This review covers both the pharmacological functions and the clinical efficacies of rikkunshito for use in treating disorders of the gastrointestinal tract.